Bends in Non-Radiative Dielectric Guide - P. Bhushan Mital (Active and Passive Electronic Components)
Curved bends in NRD waveguides have been developed. Measured insertion losses of 90º and 180º bends in an NRD guide are reported. Both the bends have insertion losses very near a reference straight guide in the frequency range from 33.5–36.5 GHZ.